Neuroimaging Markers for Differential Diagnosis Between Multifocal Motor Neuropathy and Multifocal Acquired Demyelinating Sensory and Motor Neuropathy - Taisiya A. Tumilovich; Victoria V. Sinkova; Daria A. Grishina; Natalia A. Suponeva; Sofya N. Morozova; Marina V. Krotenkova; Anna V. Mansurova; Andrey O. Chechetkin (Анналы клинической и экспериментальной неврологии, 2024)
Introduction. Similar asymmetric patterns of motor disorders and neurophysiological changes complicate the differential diagnosis between multifocal motor neuropathy (MMN) and multifocal acquired demyelinating sensory and motor neuropathy (MADSAM) as two chronic dysimmune neuropathies with significantly different treatment approaches. The lack of specific paraclinical markers often result in misdiagnosis and selection of ineffective specific therapy. Identification of specific neuroimaging biomarkers to differentiate these conditions may improve diagnostic approaches.